The assessment of craving: psychometric properties, factor structure and a revised version of the Alcohol Craving Questionnaire (ACQ) - Raabe, Almut; Grüsser, Sabine M.; Wessa, Michèle; Podschus, Jan; Flor, Herta (Addiction, 2005)
Aims The goal of the present study was to examine the psychometric properties and factor structure of the Alcohol Craving Questionnaire (ACQ). Design and participants The German version of the ACQ was administered to a sample of 243 alcohol-dependent or alcohol-abusing subjects. A subgroup of the sample (n = 46) completed the German translation of the Obsessive Compulsive Drinking Scale (OCDS) and the ACQ a second time. Measurements To validate the factor models, confirmatory factor analyses (CFA) were carried out. Examination of the psychometric properties of the ACQ included the analysis of the item characteristics to exclude non-sensitive items, an exploratory factor analysis of the remaining items and calculation of internal consistency, test-retest reliability and convergent validity. Findings Neither of the two models showed a satisfactory correspondence. An exploratory factor analysis of a revised version of the ACQ (ACQ-R), based on the psychometric properties of the items, revealed two stable factors (‘urge and intention to drink alcohol’ and ‘reinforcement’) with high internal consistency, test-retest reliability and convergent validity. The model fit was also excellent in the CFA. Conclusions The ACQ-R is a reliable and valid instrument to assess alcohol craving. However, the ACQ-R lacks items related to loss of control. Therefore a multi-dimensional assessment, e.g. the combination of the ACQ-R and the OCDS, is recommended.
Gesehen am 05.11.2020